KETERAMPILAN BERBICARA MAHASISWA CALON GURU DALAM BERINTERTERAKSI DENGAN DOSEN - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is a survey research which aims to describe the speaking skills of the prospective teacher students in interacting with their lecturers. The subjects of this research were the prospective teacher students of PGSD FIP UNM who were actively in taking the part in lectures taught by researchers (Konsep Dasar IPA, Pendidikan IPA Lanjutan, Pengembangan Konsep Dasar IPA, dan Evaluasi Pembelajaran) whose parents' work backgrounds were farmers. The population in this study was of 100 people. The sampling method uses is a quota technique. The sample size was of 80 people, obtained using the Slovin formula. The data collection techniques used were a observation and interview techniques with research instruments in the form of observation sheets, daily recording sheets and interview guides. The data analysis technique used was the descriptive data analysis technique. Research results and conclusions: In general, the students in speaking when take interacting with their lecturers demonstrated the speaking skills of "not being rude" and "thankful" every time they end a conversation with their lecturer. Meanwhile, generally, the students lack of in speaking skills in terms of: speaking correlated, not interrupting the conversation, not having a commanding tone in the conversation, being empathetic, paying attention to the time, and paying attention to the lecturer when speaking. In other words, when students speak in take interacting with lecturers, they generally lack of connection, interrupt, have a commanding tone, lack of empathy, pay less attention to the time and pay less attention to the lecturer when speaking.